The Consept of «Culturological Text» as an Effective Method to Interpretative Activity of Pupils (Proceedings of Southern Federal University. Philology, 2020)
This article deals with modern views of scholars supervisors-researchers about the concept of «culturological text» and the method of text interpretation, proves the didactic resource of the culturological text for interpretative activity of pupils. The notion of text interpretation method is introduced in the article, it demonstrates importance of background knowledge in the text understanding, shows connection between presence of pupils’ background cultural knowledge and their understanding of cultural implication of a text. The authors suggest review work variants with background cultural knowledge; analyze data of the summative assessment for revealing skills of interpretation activity of pupils, provide a number of techniques realizing the interpretation text method, offer exercises system directing to forming and developing interpretation skills. Analysis method of scientific literature, scrutiny and questionnaires of school teachers have been used in this article. The research result – an exercises system realizing stage-by-stage forming and developing interpretation skills by pupils based of the culturological texts of exercises of textbooks of the Russian language (8-9 cl.)Key words: culturological text, interpretation, interpretative activity, text interpretation method, background cultural knowledge, cultural implication, culturological comment.DOI 10.18522/1995-0640-2020-2-206-216